Factors Influencing Changes In Traditional Market Patterns (Case Study At Pasar Baru, Bangko District, Merangin Regency, Jambi Province In 2022/2023) - Arislan Arislan; Badawi Badawi; Mardalena Mardalena (Dinasti International Journal of Education Management And Social Science, 2023)
Pasar Baru Bangko is a traditional market whose buildings are partly owned by the Merangin district government and partly owned by the community (private sector). Even though there are two ownerships, they still have to be managed properly by both parties. Lately there has been a kind of change in pattern where people usually sell during the day, some have sold at night. Residents who sell things at night that seem disorganized or chaotic will cause problems such as disruption to pedestrians and motorists, disruption of environmental sanitation which can impact environmental health, disruption to shop owners, and so on. In connection with changes in market patterns that can have a negative impact even though there is a slight positive impact, it is necessary to do research. The research was conducted using a case study qualitative approach with the main data collection technique being observation supported by interviews and documentation and so on. The purpose of this research is to find out the factors that cause changes in the pattern of the new Bangko market so that it can become input for market managers, other related parties and for further researchers. The results of the study can be concluded that (1) Most of the traders in Pasar Baru Bangko have moved to selling at night due to the lack of buyers during the day; (2) It seems that the parties related to the management and control of the market are not carrying out their duties optimally due to several factors such as the lack of budget for law enforcement, especially for POL PP, UPTD Markets and so on; (3) There is no cross-sectoral cooperation, such as between POL PP, UPTD, the Department of Transportation, LH and so on, so that it seems that traders are allowing traders to sell their wares.